EDUKASI DAN SOSIALISASI PENCEGAHAN PENYEBARAN COVID-19 PADA SISWA DAN GURU SEKOLAH MENENGAH PERTAMA BERBASIS USAHA KESEHATAN SEKOLAH (UKS) DI KECAMATAN BINJAI KABUPATEN LANGKAT, PROVINSI SUMATERA UTARA, TAHUN 2020 - Rina Amelia; Arlinda Sari Wahyuni; Yuki Yunanda; , Putri Chairani Eyanoer; Juliandi Harahap; Isti Ilmiati Fujiati (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2020)
The coronavirus pandemic (COVID-19) is designated as a Public Health Emergency that is troubling the world, much remains unknown about the virus that causes COVID-19, but in general, this virus is transmitted through direct contact with droplets from the respiratory tract of an infected person (which exits through coughs). And sneezes). People can also become infected by touching a surface contaminated with this virus and then touching their face (eg, eyes, nose, mouth). The school health program (SHP) is a health program implemented at the school level. The main activities of SHP are carried out through health education, health services, and fostering a healthy school environment with the primary target of students, educators, educators, and the school community. Efforts to maintain health can be started from the school environment, which emphasizes changing behavior. Therefore this SHP program is essential because it includes early health education. This community service aims to provide education and socialization to prevent the spread of the COVID-19 virus to teachers and students based on UKS at Amanah SMPS, Binjai District, Langkat Regency. Before being given education, assessing the COVID-19 prevention behavior that they have implemented is carried out using a valid questionnaire. Then proceed with educational activities. The educational method carried out was by lecturing and discussing the prevention of COVID-19 and simulating the proper use of masks, after which several participants were asked to practice it and witnessed by other participants. It is hoped that with this community, serving students and teachers will increase their understanding and be able to prevent COVID-19 both for themselves and prevention in the community.